(untitled) (Research, Society and Development, 2020)
The practice of physical exercise is associated with several benefits, including improved quality of life (QOL). However, yet is lacking information about the influence of the weekly frequency of physical training on the general quality of life and in its different domains. Thus, the present study aimed to compare QOL levels between individuals with weekly training frequency (FS) less than or equal to three sessions and individuals with FS equal to or greater than four sessions. The study, of comparative transversal character, evaluated the general quality of life and in the physical, psychological, social and environmental domains by the WHOQOL-BREF questionnaire in practitioners of physical training in a gym in the city of Porto Alegre-RS. Seventy six people participated in the study, of both sexes, 39 of whom had moderate FS (<3 x / wk) and 37 people with high FS (> 4 x / wk). The comparison between groups was performed using the Mann-Whitney U test. As a result, the group with the highest FS presented a higher level of general QOL and in the physical domain (p < 0,05). In the psychological, social and environmental domains, the groups had similar QOL (p > 0,05). It is concluded that people who train with a frequency of four times or more per week may present better general QOL and in the physical domain compared to people with less weekly training frequency.